Penggunaan Konjungsi Koordinatif pada Naskah Pidato Prabowo Subianto saat Penetapan Presiden dalam Website news.detik.com Edisi 24 April 2024 - Mitha Putri Salsabilla; Vamsa Sharira Puppa Vagga; Zahra ‘Abidah; Nafi’ Syifaul Aini; Ahmad Hidayat Rifki; Asep Purwo Yudi Utomo; Uki Hares Yulianti; Amilia Buana Dewi Islamy (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Language as a means of communication requires knowledge that studies the right order of words so listeners can capture meaning without confusion. The science of syntax is present to help further learning about the order of conjunctions, especially coordinative conjunctions. This research is useful to expand knowledge about how coordinative conjunctions are used in speech texts. The purpose of this research is to analy Language as a means of communication requires knowledge that studies the right order of words so listeners can capture meaning without confusion. The science of syntax is present to help further learning about the order of conjunctions, especially coordinative conjunctions. This research is useful to expand knowledge about how coordinative conjunctions are used in speech texts. The purpose of this research is to analyze the types of coordinative conjunctions used in Prabowo Subianto's speech texts. The research object was based on the research needs and the use of coordinative conjunctions in his speeches to be analyzed and classified in depth. The data source was taken from news.detik.com publication on April 24, 2024, in the form of text. Qualitative descriptive approach and syntactical approach were chosen as the theoretical approach. The author obtained the data by reading the object of research and then identified it, so that the listening and recording techniques were used in this research. The agih method was used to analyze the text. The data were presented using formal and informal methods with 67 coordinative conjunctions used by Prabowo Subianto, namely "and" 40 times, "with" 9 times, "or" 1 time, "but" 2 times, "only" 3 times, "even" 1 time, "namely" 1 time, "that" 6 times, "is" 1 time, and "so" 3 times. Coordinative conjunctions play an important role in building text cohesion and the effectiveness of delivering political messages. This research highlights the role of coordinative conjunctions in oral political discourse, especially in the rhetoric of national leadership. The findings strengthen the theory of text cohesion while showing its application in political situations, with an interdisciplinary approach that combines linguistics and political communication science. ze the types of coordinative conjunctions used in Prabowo Subianto's speech texts. The research object was based on the research needs and the use of coordinative conjunctions in his speeches to be analyzed and classified in depth. The data source was taken from news.detik.com publication on April 24, 2024, in the form of text. Qualitative descriptive approach and syntactical approach were chosen as the theoretical approach. The author obtained the data by reading the object of research and then identified it, so that the listening and recording techniques were used in this research. The agih method was used to analyze the text. The data were presented using formal and informal methods with 67 coordinative conjunctions used by Prabowo Subianto, namely "and" 40 times, "with" 9 times, "or" 1 time, "but" 2 times, "only" 3 times, "even" 1 time, "namely" 1 time, "that" 6 times, "is" 1 time, and "so" 3 times. Coordinative conjunctions play an important role in building text cohesion and the effectiveness of delivering political messages. This research highlights the role of coordinative conjunctions in oral political discourse, especially in the rhetoric of national leadership. The findings strengthen the theory of text cohesion while showing its application in political situations, with an interdisciplinary approach that combines linguistics and political communication science.